PENGARUH COOPERATIVE LEARNING DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SEKOLAH DASAR - Gianistika, Chika (Penerbit Lafadz Jaya, 2025)
This study generally aims to determine the effect of cooperative learning models of discovery and expository learning on learning motivation and learning outcomes of Indonesian in Elementary Schools. The research method used is experimental research. This study uses a treatment by level 2 x 2 design with the independent variable of cooperative learning and the dependent variable of student learning outcomes in Indonesian material. This experimental study used students in the experimental group and students in the control group. In this study, the samples were class VB and class VC with the consideration that these classes can represent the population. The results of this study are: (1) Overall, there is a significant difference in student learning outcomes between those who participate in learning with the application of cooperative learning models of discovery learning and those who participate in cooperative learning with expository learning models; (2) Overall, there is an effect of cooperative learning interaction on student learning motivation in Indonesian subjects in Elementary Schools; (3) The learning outcomes of students who have high motivation and participate in learning with cooperative learning models of discovery learning are higher than students who participate in learning with cooperative learning models of expository learning; (4) The learning outcomes of students who have low learning motivation and participate in learning with cooperative learning models of discovery learning are higher than students who participate in learning with cooperative learning models of expository learning.